Understanding sedimentary systems and processes of the Hikurangi Subduction Margin; from Trench to Back-Arc. Volume 1. Issue 1 (2nd January 2022) - Strachan, Lorna J.; Bailleul, Julien; Bland, Kyle J.; Orpin, Alan R.; McArthur, Adam D.
ABSTRACT: This is the first of a two-part New Zealand Journal of Geology and Geophysics Special Issue that focuses on improving our understanding of sedimentary systems of the Hikurangi Subduction Margin, Aotearoa-New Zealand. It is amongst the world's youngest and most accessible active subduction margins and its sedimentary basins preserve a rich history of inception and ongoing evolution, spanning trench to back-arc positions. These sediments and sedimentary rocks provide a record of surface processes from the latest Paleogene to today, and reflect the spatio-temporal variability of the effects of subduction, seismicity, volcanism, evolving sediment sources, routing systems and processes, all imprinted upon by glacio-eustatic sea-level changes. The papers in this volume focus on the interplay between controlling mechanisms and the dynamics of these systems, from both onshore and offshore sedimentary environments. This issue is divided into two themes, distinguished by geological age: 1. Miocene Sedimentary Systems and intra-slope basin evolution, and 2. Insights from Quaternary Sedimentary Systems from the trench to the inner margin. Collectively, these papers represent significant advances into our understanding of sedimentary systems within the Hikurangi Subduction Margin, with innovative results that may find applications to other convergent settings.